Stages of formation of collection “Arboretum of State variety network” - О. В. Халимон (Plant Varieties Studying and Protection)
The article devotes to the stages of formation of plant collection of park of landscape and gardening art of local importance “arboretum State variety network” located in the village Oguyivka of Mashevka district of Poltava region.